2021
DOI: 10.1088/1361-648x/abdbe9
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stability, metallic character and bonding of the Si2BN planar structure

Abstract: The family of monolayered Si2BN structures constitute a new class of 2D materials exhibiting metallic character with remarkable stability. Topologically, these structures are very similar to graphene, forming a slightly distorted honeycomb lattice generated by a union of two basic motifs with AA and AB stacking. In the present work we study in detail the structural and electronic properties of these structures in order to understand the factors which are responsible for their structural differences as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Very recently, the authors of the present work have proposed a stable graphene-like single layered Si 2 BN structure that is free of dangling bonds and entirely flat with unusual sp 2 like bonding for all Si atoms [19,20]. Soon after its discovery, the Si 2 BN structure has attracted the interest of the scientific community and several reports about its potential use in a number of applications have been published since then [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Very recently, the authors of the present work have proposed a stable graphene-like single layered Si 2 BN structure that is free of dangling bonds and entirely flat with unusual sp 2 like bonding for all Si atoms [19,20]. Soon after its discovery, the Si 2 BN structure has attracted the interest of the scientific community and several reports about its potential use in a number of applications have been published since then [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 77%
“…From our preliminary calculations [38], it has been found that Si 2 BN-nanoribbons (Si 2 BN-NR) exhibit oscillating band gaps as a function of their widths. One of the major characteristics of this oscillation reveals its indirect relationship with the atomic conformation of the unit cell used in the periodic boundary conditions which are applied along its axial axis (xaxis).…”
Section: Introductionmentioning
confidence: 98%
“…The Si 2 BN is a particular 2D material that is currently attracting significant attention due to its potential use in batteries [14]. The theoretical prediction of Si 2 BN nanosheet displayed graphene-like planar structure [15][16][17], having Si-Si-B-N arrangement similar to graphene. Si 2 BN sheets show high formation energy similar to graphene and h-BN monolayers, dynamic stability, as well as stability at elavated temperatures.…”
Section: Introductionmentioning
confidence: 99%